Peran Orang Tua Dalam Meningkatkan Prestasi Belajar Siswa Di SMA Negeri 2 Muara Teweh Kabupaten Barito Utara - Rinto Alexandro; Windy Utami Putri; Fendy Hariatama; Merisa Oktaria; Sundari Sundari (FKIP, Universitas Palangka Raya, 2021)
Creating an ideal learning environment requires a perception between the family and the community. In the home environment in particular, parents are one of the factors that can affect children's learning motivation. The more children are given motivation, the children will be eager to carry out their learning activities in order to achieve learning achievement. This study uses a qualitative research type. This study involved 25 informants. The data collected in this research is by conducting observations first, then conducting interviews, and documenting the necessary data, both primary data and secondary data, then analyzed qualitatively and a conclusion is drawn. Based on the results of data analysis that has been carried out, it can be concluded that the role of parents in improving student achievement at SMA Negeri 2 Muara Teweh, North Barito Regency is still low. Parents are still less active and motivating, and pay attention to their children's learning achievements at school. This is because he is busy at work, so he doesn't have much time to pay attention to the learning achievements of his children every day. Parents believe that their children will be able to overcome all kinds of difficulties faced at school. Because, the facilities provided by parents to their children have been fulfilled. For example, transportation facilities and learning facilities, where children are included in tutoring at home, even with learning at school